Lipid bilayer thickness determines cholesterol's location in model membranes. Issue 47 (1st November 2016) - Marquardt, Drew; Heberle, Frederick A.; Greathouse, Denise V.; Koeppe, Roger E.; Standaert, Robert F.; Van Oosten, Brad J.; Harroun, Thad A.; Kinnun, Jacob J.; Williams, Justin A.; Wassall, Stephen R.; Katsaras, John
Abstract : Cholesterol is driven by hydrophobic mismatch to span the mid plane of very thin membranes. Abstract : Cholesterol is an essential biomolecule of animal cell membranes, and an important precursor for the biosynthesis of certain hormones and vitamins. It is also thought to play a key role in cell signaling processes associated with functional plasma membrane microdomains (domains enriched in cholesterol), commonly referred to as rafts. In all of these diverse biological phenomena, the transverse location of cholesterol in the membrane is almost certainly an important structural feature. Using a combination of neutron scattering and solid-state 2 H NMR, we have determined the location and orientation of cholesterol in phosphatidylcholine (PC) model membranes having fatty acids of different lengths and degrees of unsaturation. The data establish that cholesterol reorients rapidly about the bilayer normal in all the membranes studied, but is tilted and forced to span the bilayer midplane in the very thin bilayers. The possibility that cholesterol lies flat in the middle of bilayers, including those made from PC lipids containing polyunsaturated fatty acids (PUFAs), is ruled out. These results support the notion that hydrophobic thickness is the primary determinant of cholesterol's location in membranes.